Bacteriorhodopsin is involved in halobacterial photoreception. - Bibikov, S I (1993)
The bacterio-opsin gene was introduced into a "blind" Halobacterium salinarium mutant that (i) lacked all the four retinal proteins [bacteriorhodopsin (BR), halorhodopsin, and sensory rhodopsins (SRs) I and II] and the transducer protein for SRI and (ii) showed neither attractant response to long wavelength light nor repellent response to short wavelength light. The resulting transformed cells acquired the capability to sense light stimuli. The cells accumulated in a light spot, demonstrating the BR-mediated orientation in spatial light gradients. As in wild-type cells, a decrease in the intensity of long wavelength light caused a repellent response by inducing reversals of swimming direction, but, in contrast to wild-type cells, a decrease in the intensity of short wavelength light also repelled the cells. An increase in light intensity evoked an attractant response (i.e., a transient suppression of spontaneous reversals). Signal processing times and adaptation kinetics were similar to the SRI-mediated reactions. However, compared to SR-mediated photoresponses, higher light intensities were necessary to induce the BR-mediated responses. The light sensitivity of the transformant was increased by adding 1 mM cyanide and decreased by the addition of arginine, agents that respectively reduce and increase the light-independent generation of the electrochemical potential difference of H+ ions (delta mu H+). A decrease in irradiance to an intensity that was still high enough to saturate BR-initiated delta mu H+ changes failed to induce the repellent effect, but the addition of a protonophorous uncoupler sensitized the cell to these light stimuli. The BR D96N mutant (Asp-96 is replaced by Asn) with decreased proton pump activity showed strongly reduced BR-mediated responses. Azide, which increases this mutant's H+ pump efficiency, increased the photosensitivity of the mutant cells. Moreover, azide diminished (i) the membrane potential decreasing and (ii) repellent effects of blue light added to the orange background illumination in this mutant. We conclude that the BR-mediated photoreception is due to the light-dependent generation of delta mu H+. Our data are consistent with the assumption that the H. salinarium cell monitors the membrane energization level with a "protometer" system measuring total delta mu H+ changes or its electric potential difference component.